Deep Brain Stimulation of the Medial Septal Nucleus Induces Expression of a Virally Delivered Reporter Gene in Dentate Gyrus - Fomenko, Anton; Lee, Darrin J.; McKinnon, Chris; Lee, Eun Jung; de Snoo, Mitchell L.; Gondard, Elise; Neudorfer, Clemens; Hamani, Clement; Lozano, Andres M.; Kalia, Lorraine V.; Kalia, Suneil K. (Frontiers in Neuroscience, 2020)
Background Mechanisms of deep brain stimulation (DBS) remain controversial, and spatiotemporal control of brain-wide circuits remains elusive. Adeno-associated viral (AAV) vectors have emerged as vehicles for spatiotemporal expression of exogenous transgenes in several tissues, including specific nuclei in the brain. Coupling DBS with viral vectors to modulate exogenous transgene expression remains unexplored. Objective This study examines whether DBS of the medial septal nucleus (MSN) can regulate gene expression of AAV-transduced neurons in a brain region anatomically remote from the stimulation target: the hippocampal dentate gyrus. Methods Rats underwent unilateral hippocampal injection of an AAV vector with c-Fos promoter-driven expression of TdTomato (TdT), followed by medial septal nucleus (MSN) electrode implantation. Rodents received no stimulation, 7.7 Hz (theta), or 130 Hz (gamma) DBS for 1 hour one week after surgery. In a repeat stimulation experiment, rodents received either no stimulation, or two 1 hour MSN DBS over 2 weeks. Results No significant differences in hippocampal TdT expression between controls and acute MSN DBS were found. With repeat DBS we found c-Fos protein expression was induced and we could detect increased TdT with either gamma or theta stimulation. Conclusion We demonstrate that viral vector-mediated gene expression can be regulated spatially and temporally using DBS. Control of gene expression by DBS warrants further investigation into stimulation-responsive promoters for clinical applications.